PENGUNGKAPAN SUSTAINABILITY REPORT dan KOMISARIS INDEPENDEN TERHADAP PRAKTIK EARNINGS MANAGEMENT - Wibowo, Pius Kristianto; Aryanindita, Gabriel (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2025)
The obligation to disclose sustainability reports forces companies to prioritize the social and environmental dimensions, beyond the economic domain. Independent commissioners oversee corporate activities. This study examines the impact of sustainability report disclosure and the presence of independent commissioners on earnings management practices within companies. This study examined non-financial sector companies listed on IDX from 2019-2022, focusing on the IDX Main Board as of September 2023. We measured disclosure of sustainability reports, independent commissioners, and earnings management. Research data were obtained from the companies' sustainability and annual reports, which came from their official websites or the Indonesia Stock Exchange (IDX) website. The data were processed using SPSS software version 25. The data analysis methods included descriptive statistics, classical assumption analysis, and hypothesis testing. The results showed no effect of sustainability report disclosure on earnings management. However, independent commissioners had a negative effect on earnings management.